Mechanisms of Podocyte Detachment, Podocyturia, and Risk of Progression of Glomerulopathies - Hernán Trimarchi (Karger Publishers, 2020)
Background: Glomerulopathies are the main cause of ESRD. Primary or secondary causes of glomerular diseases comprise more than 70% of cases that end up in renal replacement therapies. Summary: The total glomerular mass that each individual contains is key to maintaining normal kidney function. Diabetes, hypertension, and any primary or secondary glomerulopathy may threaten the normal glomerular function. In fact, any glomerular insult may alter the glomerular filtration barrier, which in turn is composed by the podocyte, the glomerular basement membrane, and the capillary endothelial cell. Deposition of immune complexes, antibodies, or complement components at the subepithelial, intramembranous, or subendothelial space, and mutations in podocyte, slit diaphragm, or glomerular basement membrane proteins or enzymes are the main etiologies of glomerular alterations. Podocytes are glomerular cells that do not divide under normal circumstances. In this respect, maintenance of the absolute podocyte number per glomerulus is critical for normal glomerular function. As the insult progresses, podocytes start to detach from the glomerular basement membrane. When the podocyte loss is over 40% in a glomerulus, glomerulosclerosis develops, and obliteration of the glomerulus is the rule. In clinical grounds, this phenomenon is diagnosed mainly by proteinuria and a decline in glomerular filtration rate. Key messages: In this review article, the impact of podocyturia in glomerular diseases and the main mechanisms of podocyte detachment are discussed. Finally, potential targets of therapeutic approach are suggested.